Transcriptome profiling reveals male- and female-specific gene expression pattern and novel gene candidates for the control of sex determination and gonad development in Xenopus laevis - Piprek, Rafal P. (Dev Genes Evol, 2019)
Xenopus laevis is an amphibian (frog) species widely used in developmental biology and genetics. To unravel the molecular machinery regulating sex differentiation of Xenopus gonads, we analyzed for the first time the transcriptome of developing amphibian gonads covering sex determination period. We applied microarray at four developmental stages: (i) NF50 (undifferentiated gonad during sex determination), (ii) NF53 (the onset of sexual differentiation of the gonads), (iii) NF56 (sexual differentiation of the gonads), and (iv) NF62 (developmental progression of differentiated gonads). Our analysis showed that during the NF50, the genetic female (ZW) gonads expressed more sex-specific genes than genetic male (ZZ) gonads, which suggests that a robust genetic program is realized during female sex determination in Xenopus. However, a contrasting expression pattern was observed at later stages (NF56 and NF62), when the ZW gonads expressed less sex-specific genes than ZZ gonads, i.e., more genes may be involved in further development of the male gonads (ZZ). We identified sexual dimorphism in the expression of several functional groups of genes, including signaling factors, proteases, protease inhibitors, transcription factors, extracellular matrix components, extracellular matrix enzymes, cell adhesion molecules, and epithelium-specific intermediate filaments. In addition, our analysis detected a sexually dimorphic expression of many uncharacterized genes of unknown function, which should be studied further to reveal their identity and if/how they regulate gonad development, sex determination, and sexual differentiation. Comparison between genes sex-specifically expressed in developing gonads of Xenopus and available transcriptome data from zebrafish, two reptile species, chicken, and mouse revealed significant differences in the genetic control of sex determination and gonad development. This shows that the genetic control of gonad development is evolutionarily malleable. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00427-019-00630-y) contains supplementary material, which is available to authorized users.